Exchange-driven slow relaxation of magnetization in NiII2LnIII2 (LnIII = Y, Gd, Tb and Dy) butterfly complexes: experimental and theoretical studies. Issue 38 (15th September 2022) - Chakraborty, Amit; Ahmed, Naushad; Ali, Junaid; Moorthy, Shruti; Goura, Joydeb; Singh, Saurabh Kumar; Rogez, Guillaume; Chandrasekhar, Vadapalli
Abstract : A series of NiII2LnIII2 complexes (Ln III =Y (1 ), Gd (2 ), Tb (3 ) and Dy (4 )) having a butterfly-like metal core were synthesized and structurally characterized; their magnetic measurements reveal that the Ni2 Tb2 analogue possess SMM behaviors. Abstract : The tetranuclear NiII2LnIII2 complexes, [L′2 Ni(MeOH)(μ-OAc)2 (μ3 -MeO)2 Ln2 , Ln III = Y III (1 ), Gd III (2 ), Tb III (3 ), and Dy III (4 )], were prepared using a Schiff base ligand, H3 L [H3 L = 3-(2-hydroxy-3-methoxybenzylidene)amino-2-(2-hydroxy-3-methoxyphenyl)-2, 3-dihydroquinazolin-4(1 H )-one, where L′ 3− is the deprotonated open structure of H3 L]. X-ray crystallographic analysis of 1–4 revealed that all the complexes crystallized in the orthorhombic ( Pbcn ) space group, and possessed an isostructural tetranuclear butterfly or defect dicubane like core. Direct current magnetic susceptibility measurements performed on 2–4 revealed that all these complexes show an intramolecular ferromagnetic exchange coupling. Well resolved zero-field out-of-phase signals in ac magnetic susceptibility measurements were observed only in the case of 3 ( U eff = 13.4 K; τ 0 = 4.1(7) × 10 −7 s). This was attributed to the comparatively strong Ni II –Tb III magnetic exchange coupling. DFT and ab initio calculations were carried out on 1–4 to ascertain the nature of the ferromagnetic Ni II –Ln III ( J Ni–Ln ) and Ln III –Ln III ( J Ln–Ln ) interactions. Magnetic anisotropy and magnetic relaxation mechanisms were discussed in detail for 3 and 4 . Theoretical studies provide a rationale for the slow relaxation of magnetization in 3 .